Presentation a Road Map of Service Quality for Travel Agencies by SERVQUAL and REMBRANDT - Amir Karbassi Yazdi; Bahar Beishami (تحقیقات کاربردی علوم جغرافیایی)
The aim of this research is to identify and prioritize impact factors of service quality in Tourism Industry. Today, Tourism knows as the most important factors for incoming of countries and Iran is one of the 10th best countries about site seeing. Hence, based on rules, the dependency of Iran’s budget on oil have to decrease. The trip is one of the most important things for each Iranian's family. Therefore, the quality of services in the tourism industry can effect on the quantity of trips. So, these factors must be identified and then the rare resources of travel agencies are allocated to them. One of the evaluation models of service quality is Servqual that has 5 criteria such as reliability; responsiveness; assurance; empathy and tangibles which each of these criteria has sub-criteria. Travel agencies can implement this model and evaluate the service quality of them. But after identification of these factors, allocation of these rare resources such as HR, budget, time for implementing improvement programs is the most important factors for each agency. Hence, for allocating rare resources of travel agencies, Rembrandt method is used. Statistics society of this research is all passengers who travel in other in the internal or external city of Iran during Esfand month. This research is done by survey and sampling did by random. The result shows that among five criteria, sympathy criterion has high priority and among sub-criteria, creating trust in customer has high priority.